2012
DOI: 10.1634/theoncologist.2011-0385
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Mutation Heterogeneity and the Mixed Response to EGFR Tyrosine Kinase Inhibitors of Lung Adenocarcinomas

Abstract: Background. Non-small cell lung cancer patients with epidermal growth factor receptor (EGFR) mutations have mixed responses to tyrosine kinase inhibitors (TKIs). Intertumor heterogeneity in EGFR mutations is one potential explanation for this phenomenon.Methods. We performed direct sequencing to identify EGFR mutations in 180 pairs of lung adenocarcinoma samples (from 3,071 patients). The high-resolution melting method was used in discordant cases to confirm EGFR mutation status. Matching samples were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 30 publications
7
120
2
3
Order By: Relevance
“…Candidate recipients include patients with lesions difficult for biopsy sampling, those with obscure biopsy results, and those who prefer not to have biopsy. The presence of intertumor heterogeneity of EGFR mutations (19 ) indicates that the mutation status of primary lesions may not represent that of metastatic lesions. Because ctDNA includes DNA from both lesions, mutation screening with plasma DNA may be beneficial to detect mutations in lesions other than biopsy sites.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate recipients include patients with lesions difficult for biopsy sampling, those with obscure biopsy results, and those who prefer not to have biopsy. The presence of intertumor heterogeneity of EGFR mutations (19 ) indicates that the mutation status of primary lesions may not represent that of metastatic lesions. Because ctDNA includes DNA from both lesions, mutation screening with plasma DNA may be beneficial to detect mutations in lesions other than biopsy sites.…”
Section: Discussionmentioning
confidence: 99%
“…The authors attempted to explain this apparent inconsistency in terms of the heterogeneity of genetic tumour abnormalities, where tumour cells may or may not carry the mutation. A recent study has demonstrated a high discordance rate among multiple pulmonary nodules in terms of EGFR mutation, emphasizing the problem of tumour heterogeneity (90) and suggesting that CTC or circulating DNA analyses are crucial in the identification of the presence of mutations and tumour heterogeneity.…”
Section: Biological Samples Suitable For Molecular Characterisationmentioning
confidence: 99%
“…Consequently this can be of use in guiding further treatment and predicting survival in cancer patients (6,7,9).…”
Section: Discussionmentioning
confidence: 99%
“…With advances in high-throughput technologies, such as next-generation sequencing, intra-or inter-tumoral genomic heterogeneity has been highlighted in the area of molecular oncology and can improve our understanding of this response (8). For example, inter-tumoral heterogeneity of an EGFR mutation has been well described in adenocarcinoma (9). Therefore, the HRR leads clinicians to switch to another anticancer regimen due to the clinically high suspicion of resistance, as histological confirmation is not feasible in the majority of cases.…”
Section: Introductionmentioning
confidence: 99%